Deskripsi Kemampuan Komunikasi Matematis Siswa Berkemampuan Matematika Tinggi Ditinjau dari Perbedaan Gender - Firman; Alimuddin; Nurwati Djam’an (Issues in Mathematics Education (IMED), 2017)
This research is a qualitative research that has a purpose to describe mathematical communication ability of students with high level mathematical ability in solving mathematics problem with regards to gender differences in material system of linear equation in two variabels. The subjects in this research were 2 students on grade VIII, that is one male student with high level mathematical ability (KTL) and one female student with high level mathematical ability (KTP). For data collection, the instruments used are written test and interviews. The results showed that (1) in the process of analyze and evaluate the mathematical ideas and solving strategies, the subject KTL be able to analyzed and evaluated the mathematical ideas on the problem well, while the subject KTP did not be able to analyzed and evaluated the mathematical ideas on the problem well; (2) in the process of communicate their mathematical thinking coherently and clearly, the subject KTL do every step with a complete and detailed procedure but are not adept at using alternative/other procedures to solve the problem given, while the subject KTP does every step with a concise yet advanced procedure using alternatives/other procedures to resolve the given problem; and (3) in the process of use the language of mathematics to express mathematical ideas precisely, both subjects used and well understood some of the mathematical modeling and models used in solving the problems.